Larval features of the Italian endemic Pyrochroa serraticornis kiesenwetteri Fairmaire, 1849 (Coleoptera: Pyrochroidae: Pyrochroinae) solve taxonomic uncertainties - Molfini, Marco; Bologna, Marco A. (Zootaxa, 2023)
Recent findings rearranged the taxonomy of the European species of the genus Pyrochroa Geoffroy (Coleoptera: Pyrochroidae), and to date three species are recognized: P. bifoveata Molfini et al., 2022 and P. coccinea (Linnaeus, 1761) with cryptic adults and distinctive larvae, and the polytypic P. serraticornis (Scopoli, 1763), including the subspecies kiesenwetteri Fairmaire, 1849. Incongruences between molecular and morphological analyses questioned the recognition of P. s. serraticornis and P. s. kiesenwetteri as taxa of the same species. In the present paper, observations of larval characters of P. s. kiesenwetteri confirm this taxon as a subspecies of P. serraticornis. Moreover, new characters of P. s. serraticornis larvae are offered by analysing specimens from a new European locality.